Bernini and the bell towers architecture and politics at the Vatican - McPhee, Sarah 1960- (Yale University Press, 2002)
"In 1638, the great artist-architect Gianlorenzo Bernini began one of the most ambitious architectural projects of his career: to design and construct massive twin bell towers atop St. Peter's basilica at the Vatican. But the project failed spectacularly. Bernini's reputation was permanently tarnished, and the scandal of the bell towers sparked a controversy that persists to this day. What happened? Who was responsible? How did events unfold in this dramatic episode of architectural history?"--Publisher's description